2009
DOI: 10.1007/s10557-009-6205-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Difficulties in Measuring HDL Subfractions and Human Paraoxonase-1 Activity During Statin Treatment

Abstract: Dyslipidaemia including decreased high density lipoprotein cholesterol concentration is one of several factors that have been implicated in increased cardiovascular risk. Since their introduction in the 1980s, 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) have emerged as the one of the best-selling class of medications to date, with numerous trials demonstrating powerful efficacy in preventing cardiovascular diseases. Although statins have been shown to modestly raise or not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 95 publications
0
21
1
1
Order By: Relevance
“…24 Statins, apart from the capacity of lowering cholesterol levels by inhibiting the enzyme HMG-CoA reductase, provide anti-oxidative protection by increasing PON1 mass and activity. 16 Considering that 35-40% of the patients of our study were under statin therapy, we may assume that in those patients statins have protective effect on PON1 levels, a fact that was confirmed by the increase of HDL3-C and not HDL2-C levels. As known, HDL3-C subclass constitutes a large proportion of antioxidant enzymes within HDL, including PON1, whereas HDL2-C is mostly involved in removal of cholesterol in patients with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…24 Statins, apart from the capacity of lowering cholesterol levels by inhibiting the enzyme HMG-CoA reductase, provide anti-oxidative protection by increasing PON1 mass and activity. 16 Considering that 35-40% of the patients of our study were under statin therapy, we may assume that in those patients statins have protective effect on PON1 levels, a fact that was confirmed by the increase of HDL3-C and not HDL2-C levels. As known, HDL3-C subclass constitutes a large proportion of antioxidant enzymes within HDL, including PON1, whereas HDL2-C is mostly involved in removal of cholesterol in patients with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 65%
“…15 On the other hand, it has been found that statin therapy can increase PON1 activity in combination with HDL-levels and cholesterol efflux capacity in dyslipidemic patients. 16,17 CONTACT The present study aimed to compare PON1 concentration in patients with renal failure (RF) and CKD patients on HD, without or with statin therapy. We also analyzed the association of PON1 with lipids, lipoproteins, apolipoproteins, as well as HDL2 and HDL3-C subclasses, which concur in different way to HDL-C protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, parallel to this lack of difference between lipid profiles, no correlation between the lipid profile and Gensini score was observed. Several reports have investigated the effect of lipid-lowering therapy or drugs on PON1 activity and expression 49) . Although in the majority of clinical studies it has been shown that serum PON1 activity was modestly increased in patients taking lipid-lowering therapy, no consensus has been reached, probably due to population heterogeneity and assay method differences.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it must be noted that lipid lowering agents, such as statins [12,13] , fibrates [14] and ezetimibe [15] have a significant effect on HDL composition and function. Consequently, evaluating the effect of various lipid abnormalities on HDL properties in patients on lipid lowering therapy can be misleading [16] . Therefore, we investigated the structural and some functional HDL proper ties in newly diagnosed, untreated dyslipidemic patients and in healthy controls to evaluate the effect of dyslipidemia on the structural and functional properties of HDL characterized by the serum levels of HDL subfractions and MPO, PON1 paraoxonase and arylesterase activities and PON1 phenotyping.…”
Section: Introductionmentioning
confidence: 99%